Lens-induced glaucoma, a collateral damage during COVID-19 Pandemic - Shankari S,; Jemaima CH, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Cataract if left untreated, can lead to complications such as lens induced glaucoma and permanent visual loss. The COVID-19 outbreak resulted in movement control orders causing closure and reduction of non-COVID hospital services resulting delayed appointment dates. This study described the side effects of delayed patient appointments due to COVID-19 pandemic. A 70-year-old man presented with right eye (RE) pain and redness. There was gradual reduction in RE vision over the last year but treatment was delayed due to pandemic. In examination, visual acuity on his RE was hand movement and left eye (LE) was 6/12 (ph6/12) and near vision of N5. The right pupil was mid-dilated, reacting sluggishly with presence of relative afferent pupillary defect. Intraocular pressure (IOP) on the RE was 54 mmHg and LE was 16 mmHg. Circumciliary injection of right conjunctiva with central corneal haziness was seen. The anterior chamber was deep with the presence of 3+ cells with whitish lens material at the pupillary axis. A Morgagnian cataract with phacodonesis was present. A diagnosis of lens induced glaucoma was made. Immediate reduction of IOP included topical and systemic medication and pain relief were instituted. Intracapsular cataract extraction with anterior vitrectomy and surgical peripheral iridectomy was performed. This highlights the late presentation of a patient with mature cataract during the COVID-19 pandemic. Patient awareness and education are essential in recognising the complications of mature cataract if it is presented later. A reminder of signs and symptoms of lens induced glaucoma should be conveyed to patient when appointment is delayed.